The charge transport process at gold electrodes modified by thick nickel hydroxide films. A study employing rotating disc electrode voltammetry in the presence of the Fe(CN)6 3 −/4 − redox couple - Tucceri, Ismael Ricardo (2016)
Rotating disc electrode voltammetry (RDEV) was employed to study the transport properties of nickel hydroxide films electrochemically deposited on gold in the presence of the Fe(CN)6 3 −/4 − redox couple. Gold electrodes coated with nickel hydroxide surface coverages within the range 0.7 nmol cm− 2 < ΓNi(OH)2 < 55 nmol cm− 2 were obtained. Steady-state current vs. potential (I-E) dependences at different electrode rotation rates within the range 50 rpm–5000 rpm were recorded for each ΓNi(OH)2 value. While the anodic limiting current at the different nickel hydroxide surface coverages followed the Levich equation, the cathodic limiting current only responded to the Levich relationship within the ΓNi(OH)2 range comprised between 0.7 nmol cm− 2 and 16 nmol cm− 2. The cathodic limiting current at ΓNi(OH)2 values higher than 25 nmol cm− 2 responded to a reactant membrane diffusion phenomenon within the nickel hydroxide film. The cathodic process for thick nickel hydroxide films was associated with the physical diffusion of the Fe(CN)6 3 − species across the film to be reduced at the gold surface. A diffusion constant for the Fe(CN)6 3 − species dependent on the nickel surface coverage was obtained. Although the Fe(CN)6 4 − oxidation seemed to occur by a rapid electron-transfer process, a limiting electron-transport rate was observed at ΓNi(OH)2 values higher than 40 nmol cm− 2 and at high electrode rotation rates (> 7000 rpm).